Answers

2015-07-09T19:39:40+05:30
2gs = v²-u²                                                                                                        g = -9.8                                                                                                             v=0
2×-9.8 ×s =0 - u² 
               =-u²
-196*s=-u²
s=-u²/-196
 =u²/196  
h=u²/196 
0
2015-07-09T22:08:24+05:30
2gs =v power 2 -u power 2
-9.8
 2x(9.8)x s=0-u power2
                       =-u power2
-198 x 5 =-u power2
s =- u power 2\ - 196
=u power2 \196
h=u power 2\ 196
  
0